Análisis de la evolución de la recaudación tributaria por recursos determinados en la Municipalidad Distrital de Belén, periodo 2016 - 2020 - Shapiama Pérez, Sonia Patricia (2022)
Municipal tax collection is the set of measures, designed and adopted by a municipality, through which and in accordance with the law, the right to collect taxes is made to the citizens of its jurisdiction, with the purpose of increasing the level of collection in order to have the necessary public resources to finance the public spending that will be executed in a given period. This research entitled "Analysis of the Evolution of Tax Collection by Determined Resources in the District Municipality of Belén, period 2016 – 2020”, has as its objective to determine the evolution of tax collection for the study period. Likewise, the research was of a quantitative type and a non- experimental descriptive design – cross-sectional. From the results submitted to an analysis and subsequent discussion, it has been possible to determine that the tax collection with respect to the study period presents a negative evolution in the aforementioned municipality.